2014
DOI: 10.4049/jimmunol.1301294
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa–Induced Apoptosis in Airway Epithelial Cells Is Mediated by Gap Junctional Communication in a JNK-Dependent Manner

Abstract: Chronic infection and inflammation of the airways is a hallmark of cystic fibrosis (CF), a disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. The response of the CF airway epithelium to the opportunistic pathogen Pseudomonas aeruginosa is characterized by altered inflammation and apoptosis. In this study, we examined innate immune recognition and epithelial responses at the level of the gap junction protein connexin43 (Cx43) in polarized human airway epithelial cells upon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…Although to reach late stages of apoptosis upon their induction by P . aeruginosa infection epithelial cells need times longer than those used in our settings [26, 27], we checked whether P . aeruginosa infection increased the number of apoptotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although to reach late stages of apoptosis upon their induction by P . aeruginosa infection epithelial cells need times longer than those used in our settings [26, 27], we checked whether P . aeruginosa infection increased the number of apoptotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Both heat‐killed PAO1 and its lysate induced cytotoxicity in short time exposed Mo7e cells, whereas with longer exposure we observed cytotoxicity only with lysate. Earlier studies have reported that P. aeruginosa infection induces apoptosis in NK cells, macrophages and airway epithelial cells in a caspase 9 dependent manner and through interactions between cytotoxins (exoenzymes S, T and U) and host cells. Similarly, pyocyanin and exotoxin A of P. aeruginosa have also been reported to induce cytoxicity in neutrophils and mouse fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL4 binds to bacteria[ 22 , 23 ] and activates neutrophils through multiple intracellular signals and pathways[ 24 ]. Previous studies have shown essential roles for PI3K[ 25 ], Syk[ 26 ], JNK[ 27 ], p38[ 28 ] and JAK/STAT[ 29 , 30 ] signaling during host defense against P . aeruginosa , suggesting a potential role of CXCL4 in P .…”
Section: Introductionmentioning
confidence: 99%